Picking the length: investigating how bowling length influences batter decision-making in international men`s 50-over cricket - Mehta, S.; Phatak, A.; van der Kamp, J.; Jamil, M.; Savelsbergh, G.; Memmert, D. (International Journal of Performance Analysis in Sport, 2024)
In this study, 19,587 balls bowled by fast bowlers across two One-Day International (ODI) cricket tournaments were analysed, with the aim of exploring the relationship between bowling lengths and foot-based batter decision-making. Initially, a Chi-Square test of independence was used to determine if bowling lengths were associated with the foot-based decision-making of batters. Subsequently, the relationship of specific foot-based strokes with different bowling lengths were further examined through a Logistic Regression. Post-Hoc analysis of standardised residuals from Chi-Square tests suggest an association between foot-based decision-making and dot balls (?2(1) = 99.798, p < .001). Furthermore, Logistic Regression results reveal that all length zones except the half-tracker length show statistically significant association with front-foot and back-foot strokes. Respective coefficients of these length zones also show an organisation of specific strokes with front-foot stroke dominating lengths close to the batter (yorker, full-toss, half-volley and good length) and back-foot strokes dominating zones further away from the batter (back of a length and short length). The results confirm interdependence between batter-bowler performances and suggest that batters in ODI cricket prefer meeting the ball on the front foot in their search of scoring runs.